THE IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL IN THEMATIC LEARNING FOR 4TH GRADE STUDENTS TO IMPROVE THE STUDENTS’ CRITICAL THINKING SKILLS - Muhammad Syaiful Hakim; Mawardi Mawardi; Krisma Widi Wardani (Universitas Negeri Medan, 2019)
Abstract : The Implementation Of Problem-Based Learning Model In Thematic Learning For 4th Grade Students To Improve The Students’ Critical Thinking Skills. The aim of this research is to know whether the students’ thinking skills can be improved through PBL model and to know the most suitable PBL steps which can improve the critical thinking skills of 4th grade students of Koripan 01 Public Primary School, second semester, the academic year of 2018/2019. The type of this research is Classroom Action Research (CAR). In conducting this research, researchers used the C. Kemmis and Robin Mc. Tanggar model which consisted of four main activities, namely planning, implementing, monitoring, and reflecting in each cycle. Subject of this research are 24 4th grade students of Koripan 01 Public Primary School. The method of collecting data is by using observation sheet containing assessment rubric. The result shows that the improvement of learning creativity in thematic learning through PBL with a comparison between cycle I to cycle II which is increasing as much as 62% of all students. Critical thinking skills are very high clarification in cycle I which has a score of 13% increasing to 75% of all students in cycle II. The steps of PBL model used to improve the students’ critical thinking are 1) orienting the student to problems, 2) organizing the students to study, 3) guiding the individual or group study, 4) developing and presenting the result, and 5) analyzing and evaluating the problem-solving process. Keyword: Critical Thinking Skills, Problem-Based Learning, Thematic for 4th grade Abstrak: Penerapan Model Problem Based Learning dalam Pembelajaran Tematik Kelas 4 Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik. Tujuan penelitian ini yaitu untuk mengetahui apakah peningkatan keterampilan berpikir kritis peserta didik dapat diupayakan melalui model PBL serta untuk mengetahui bagaimanakah langkah-langkah PBL yang dapat meningkatkan keterampilan berpikir kritis peserta didik kelas 4 SDN Koripan 01 semester 2 tahun pelajaran 2018/2019. Metode dari penelitian ini adalah penelitian tindakan kelas atau sering disebut juga dengan PTK. Dalam pelaksanaan penelitian ini, peneliti menggunakan model C. Kemmis dan Robin Mc. Tanggar yang terdiri dari empat kegiatan pokok yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi dalam setiap siklusnya. Subjek penelitian ini adalah peserta didik kelas 4 SDN Koripan 01 yang berjumlah 24 peserta didik. Teknik pengumpulan data dilakukan dengan observasi dengan menggunakan lembar observasi berisikan rubrik penilaian. Hasil dari penelitian menunjukkan bahwa terdapat peningkatan kreativitas belajar pada pembelajaran tematik yang di lakukan melalui model PBL dengan perbandingan antara siklus I ke siklus II yakni menigkat sebanyak 62% dari seluruh peserta didik. Keterampilan berpikir kritis klarifikasi sangat tinggi pada siklus I yaitu mempunyai skor 13% meningkat menjadi 75% dari seluruh peserta didik pada siklus II. Langkah-langkah pembelajaran PBL untuk meningkatkan keterampilan berpikir kritis peserta didik adalah 1) mengorientasikan peserta didik kepada masalah, 2) mengorganisasikan peserta didik untuk belajar, 3) membimbing penyelidikan individu/kelompok, 4) mengembangkan dan menyajikan hasil karya, dan 5) menganalisa serta mengevaluasi proses pemecahan masalah. Kata Kunci : Keterampilan Berpikir Kritis, Problem Based Learning, Tematik Kelas 4